The Transcription Factor MYB37 Positively Regulates Photosynthetic Inhibition and Oxidative Damage in Arabidopsis Leaves Under Salt Stress - Li, Yuanyuan; Tian, Bei; Wang, Yue; Wang, Jiechen; Zhang, Hongbo; Wang, Lu; Sun, Guangyu; Yu, Yongtao; Zhang, Huihui (Frontiers in Plant Science, 2022)
Here we report that overexpression of MYB37, a R2R3 MYB subgroup 14 transcription factor in Arabidopsis thaliana, confers hyposensitive phenotypes to exogenous salt. The results showed that compared with the wild type (Col-0), the overexpression of MYB37 significantly alleviated the salt stress symptoms of A. thaliana plants under NaCl stress. There was significantly less of a decrease in the contents of Chl a and Chl b in OE-1 and OE-2 compared with those in Col-0. In particular, the Chl a/b ratio was also higher than that in Col-0 under NaCl stress. MYB37 alleviated the degradation of chlorophyll, particularly the decrease of Chl a in Arabidopsis under NaCl stress. The results of chlorophyll fluorescence parameters showed that NaCl stress inhibited the activities of PSII and PSI in Arabidopsis leaves, but the activity of PSII electron donor side OEC was not affected by salt stress. MYB37 increased photosynthesis in Arabidopsis by increasing the activities of PSII and PSI of Arabidopsis under NaCl stress. In addition, MYB37-overexpression increased the Y(II) and Y(NPQ) of Arabidopsis under NaCl stress but decreased Y(NO). This indicates that it increased the activity of PSII and regulated the proportion of energy dissipation in Arabidopsis leaves under NaCl stress, and it decreased the proportion of inactivated reaction centers. NaCl stress causes excess electrons and energy in the photosynthetic electron transport chain of Arabidopsis leaves, resulting in the release of ROS, such as O2- and H2O2, which results in oxidative damage. However, MYB37 reduced the accumulation of malondialdehyde in Arabidopsis leaves under NaCl stress and alleviated the degree of membrane lipid peroxidation caused by ROS. NaCl stress also led to the accumulation of SS and Pro in Arabidopsis leaves to reduce the damage of salt stress to plants and led to the degradation of SP. Because MYB37 in Arabidopsis OE-1 and OE-2 resulted in plants that suffered less damage under NaCl stress, the accumulation of osmoregulation substances SS and Pro was not shown to be higher than that in Col-0. Thus, MYB37 could alleviate the degradation of Arabidopsis proteins under NaCl stress, promote plant growth and improve its salt tolerance.